Transformations de l’agriculture et reconfiguration des terroirs au Sud-Mali : une “pression démographique” à relativiser - Sébastien Bainville; Marc Dufumier (Belgeo)
Despite the rainfall decrease and a heavy demographic growth, Southern Malian agriculture has considerably changed during the past three decades. The Malian Company of Textiles (CMDT) provided technical assistance and cotton production endowed peasants with credits. With the acquisition of animals and harnessed equipments, many farmers could replace their former slash and burn cropping systems by permanent cultivation so that fields are cultivated every year, without a fallow period. These fields are located on a more or less fertilized ager with organic matters coming from reverted lands used for animal grazing (saltus). During that period some farmers have also been diversifying their farming systems. Nowadays, the better off families gradually cease growing cotton, and develop other commercial productions (corn, bananas, mangos, cashew nuts, animal breeding, etc). Nevertheless, because they lack equipments, many peasants cannot live on agriculture only and depend on extra-agricultural income opportunities. Changes in agriculture and rural areas will also be contingent upon the evolution of land property rights: some families start enclosing low land areas to grow perennial or vegetable crops, and new relationships will probably have to be worked out between sedentary farmers and transhumant stockbreeders.